Loading dependency of 2D MoS2 nanosheets in the capacitance of 3D hybrid microfibre-based energy storage devices. (October 2021) - Roy, Anup K; Faisal, Shaikh N; Spickenheuer, Axel; Scheffler, Christina; Wang, Jiawei; Harris, Andrew T; Minett, Andrew I; Islam, Mohammad S
Highlights: Spin composite micro-fibres of 2D liquid crystalline graphene oxide and exfoliated MoS2 nanosheets with very high MoS2 loading of up to 69 wt%. The liquid crystallinity of GO induces birefringence in the composite dispersion and enables the spinning of the composite dispersion with high loading of MoS2 with great flexibility. Obtain high areal capacitance of 282.6 mF cm −2 with good cycling stability (82.5% capacitance retention after 5000 cycles) indicating high potential of these composite fibres as energy storage system for smart textile of the future. Abstract: This study reports a wet spinning method to spin composite micro-fibres of 2D liquid crystalline graphene oxide (GO) and exfoliated MoS2 nanosheets with very high MoS2 loading. The MoS2 dispersion was found to be isotropic irrespective of solvent type or solute concentration in the dispersion and thus found to be non-spinnable via wet spinning process. The liquid crystallinity of GO induces birefringence in the composite dispersion and enables the spinning of the composite dispersion containing high loading of MoS2 with great flexibility. We were able to spin composite microfibers with 69 wt% MoS2 loading for the first time. The resulting fibres were annealed at high temperature to produce flexible conductive rGO#MoS2 fibres. Scanning electron microscopy (SEM) and Raman analysis strongly suggest homogeneous distribution of MoS2 throughout the fibres. Mechanical properties of the fibres were studied and maximum tensile strength (76.5 MPa) and Young's modulus (13.3 GPa) obtained with 10 wt% MoS2 loading. All solid-state flexible symmetric supercapacitor from these composite fibres was fabricated and the electrochemical performance was studied. The electrochemical study shows high areal capacitance of the produced composite fibres (as high as 282.6 mF cm −2 ) with good cycling stability (82.5% capacitance retention after 5000 cycles) that indicates high potential of these composite fibres as energy storage system for smart textile of the future.